O circuito-cena e.music de João Pessoa: dinâmicas locais de uma cultura jovem global - D'allevedo, Pedro Tadeu Faria (2011)
The research tries to understand the way by which the electronic music culture is signified in the urban space of João Pessoa. This comprehension passes through the conformation of a festive setting circuit that, on a certain way reflects assumptions and significances of certain places of the urban space by the young people who affiliate to it. This culture with the youthful character of contemporaneity was gestated in England at the second half of the eighties and, in a short time, assumed an eminent transnational character, arriving to lead in the urban space of João Pessoa city at the end of the 90´s. At some measure, this young cultural practice has as a characteristic to fuse diversion with commercial activity, when it manifests itself at the city´s night leisure sphere through parties, bars and night clubs, and whose dynamics can be observed through social practices that youth, from them, develop in the urban and social environment. It´s appearance at the capital of Paraíba came linked to the electronic music genre and to the different themes that form it, which are very consumed and appreciated by society´s medium and high stratums. This way, this report pretends to emphasize social, cultural and behavioral practices that people build from dancing meetings that youthful culture itself makes in these urban and social contexts. The report was developed using ethnographic procedures, especially because the active observation offered a close and internal look of the investigated phenomenon, at the same time that tries to interlace three lines of reflection: the youthful culture, the social actors and the city.